(untitled) (Global Journal of Management and Business Research, 2015)
This paper discusses how the environment influences changes in the organization in this 21 st century new economy, where people tend to care more for services provided rather than the manufacturing process. It’s very important for the organization to know what environmental factors can cause the organization to change.